PRACTICAL MODELLING ASPECTS FOR FINITE ELEMENT ANALYSIS OF SHEAR WALLS - Sambu Potty, Narayanan; W.A.M., Thanoon; Hariri Bin Hamzah, Helmy; Musa Mahgoub Hamadelnil, Abdelrahim (2008)
Shear wall, a continuous vertical member, is an important element in high-rise buildings, which provides the lateral stability and resists the lateral forces resulting from earthquake and wind forces. Finite Element Method is widely used for analyzing complicated structural systems. Although many textbooks describe theoretical aspects of finite elements for modelling shear walls and its analysis, no practical advice is available to use this technique. The selected structural model must be simple, capable of producing accurate result and be economical. Different elements used in modelling shear walls are beam/column element (simplest element used for frame structure), two dimensional element, shell element and solid element. Important factors affecting the analysis of shear wall structure are the type and number of elements, the distribution of the forces, geometry and section properties and arrangement of members. The aim of this study is to investigate the suitability, simplicity, accuracy and effectiveness of different structural models used in the analysis of shear wall and coupled shear wall structures. Commercially available software is used for static and dynamic analysis of shear wall without and with openings of different sizes and arrangements. The structural behaviour in terms of deformation, stress distribution and dynamic characteristics are presented and discussed.